Ownership of Public Parking Lots Controlled by Individuals (Case Study in Cirebon City) - Vellita, Adriana; Fatah Alfiandi, Muhammad Rasyid; Nurfandhyca, Dendhy; Yusup Permana, Deni; Dikrurahman, Diky (Ann Publisher, 2025)
Background. Parking is a public necessity that initially serves a function. Following this function, parking spaces are adjusted to demand and the needs of people who drive to be or access a place. Aim. Evaluation The case that occurred in the Cirebon city area was in the market area of Jalan Kedrunan II. What happened was that one of the residents controlled the parking lot, which covered the public road, resulting in congestion and difficulty accessing the area. Methods. Normative Juridical Research is legal research that focuses on written rules or laws (laws in books) or research based on rules or norms that apply in society. It is usually said to be literature review research, where most data sources are secondary and tertiary legal materials. Most of the data comes from written laws or regulations that apply in society. Result. Local governments have duties, obligations, and responsibilities in developing and managing parking in their area, which is essentially part of public service activities. In return for organizing the public services in question, local governments have the right to receive funds from the community through retribution or taxes as one of the sources of local revenue. Following this function, parking spaces are public facilities used by many people. So, as one of the public facilities, parking spaces should not be controlled by certain people personally and prevent others from using them. But in reality, there is often a misuse of the function of parking spaces, for example, controlling parking lots to be used for personal gain. Conclusion. The research results in this paper are the basis for parking management carried out by the Cirebon City Transportation Office based on the provisions of Cirebon City Regional Regulation No. 11 of 2019 concerning Parking Management.